Improved in-vitro propagation protocol for hermaphrodite papaya (Carica papaya L. cv. eksotika) - Hashim, Halimah (2022)
Carica papaya cv. Eksotika is one of the most popular papaya varieties with high economic value in Malaysia. Generally, papaya is propagated by seeds. Being a dioecious species, bearing exclusively either male or female flowers on separate plants, seed propagation yields a mixture of male, female, and hermaphrodite papayas, each type bears variations of fruiting capabilities and fruit qualities. Micropropagation has been labelled as the most reliable system of propagation producing true-to-type hermaphrodites suitable for large-scale cultivation of papaya. However, at the onset of the procedure, micropropagation is often hampered, among others, by slow explant initiation and multiplication, as well as production of abnormalities in shoot and root structures. The present study was conducted to establish a reliable set of procedures in the production hermaphrodite papaya, Eksotika through selection of various explants' maturity stages, culture media manipulations by optimizing requirements for plant growth regulators (PGR), procedures in subculture, pretreatments in root initiation, in vitro root media substrates and plantlet performance in ex vitro environment. Shoot initiation with different explants maturity were conducted on 3-, 6-, 9- and 12-weeks old explants sourced from verified hermaphrodite papaya seedlings on Murashige & Skoog (MS) and De Fossard (DF) media, each supplemented with 1-Naphthaleneacetic acid (NAA) and 6-benzylaminopurine (BAP) in a complete randomized design (CRD) with four replications. Six-week-old explants recorded the highest rate of survival and number of shoots and leaves when cultured on DF medium supplemented with 0.1 and 0.5 mg/L NAA and BAP respectively. Shoot length was highest on DF medium supplemented with 0.1 and 0.25 mg/L NAA and BAP respectively. Multiplication rate on subculturing of adventitious buds increased gradually until the eight subcultures, but declined after the ninth. In rooting, indole-3-butyric acid (IBA) at 2.0 mg/L significantly stimulated root growth, and increased root number and length. In acclimatization, growing medium of mixture of peat moss, sand, and vermiculite in a ratio of 2:1:1 (v/v) showed significant positive effects on survival percentages, plant height, leave number, and stem diameter. Vermiculite in half-strength DF liquid medium promoted root development, producing higher root formation, number of roots, and root length. Plantlets treated with zeolite in the same medium or sterile water yielded lower rate of growth and abnormal roots development. Anatomical observations revealed that length of root hairs became significantly shorter and scattered in distribution with unicellular root hairs on the epidermal cell surfaces. In ex vitro conditions, rooted plantlets grown in vermiculite substrate showed highest survivability after transplantation in a mixture of peat moss, sand, and vermiculite in a ratio of 2:1:1 (v/v) compared to those plantlets grown in perlite, rock wool and zeolite substrates. Overall, the results proved the efficiency of micropropagation procedure to produce in vitro hermaphrodite Carica papaya L. cv. Eksotika. Papaya using shoot tips as a potential region for shoot initiation and proliferation of explants to ascertain an effective protocol for the multiplication of planting materials. Additionally, the high potential to improve the rooting phase with these findings suggests that the rooting substrate may induce considerable changes in root quality which in turn affects plantlets survival during acclimatization. Solving these issues, it can help improve the protocol that will produce a high success rate in the mass production of true-to-type hermaphrodite Carica papaya cv. Eksotika and high-quality plants